Does the CT improve inter- and intra-observer agreement for the AO, Fernandez and Universal classification systems for distal radius fractures? - Arealis, Georgios; Galanopoulos, Ilias; Nikolaou, Vassilios S; Lacon, Andrew; Ashwood, Neil; Kitsis, Christos (Injury, 2014)
INTRODUCTION: Distal radius fractures are very common upper limb injuries irrespective of the patient's age. The aim of our study is to evaluate the reliability of the three systems that are often used for their classification (AO - Arbeitsgemeinschaft für Osteosynthesefragen/Association for the Study of Internal Fixation, Fernandez and Universal) and to assess the need for computed tomography (CT) scan to improve inter- and intra-observer agreement. MATERIALS AND METHODS: Five orthopaedic surgeons and two hand surgeons classified radiographs and CT scans of 26 patients using the Fernandez, AO and Universal systems. All data were recorded using MS Excel and Kappa statistics were performed to determine inter- and intra-observer agreement and to evaluate the role of CT scan. RESULTS: Fair-to-moderate inter-observer agreement was noted with the use of X-rays for all classification systems. Intra-observer reproducibility did not improve with the addition of CT scans, especially for the senior hand surgeons. CONCLUSIONS: The agreement rates observed in the present study show that currently there is no classification system that is fully reproducible. Adequate experience is required for the assessment and treatment of these injuries. CT scan should be requested only by experienced hand surgeons in order to help guide treatment, as it does not significantly improve inter- and intra-observer agreement for all classification systems.
Keywords: Humans; Observer Variation; Professional Competence; Radius Fractures; Reproducibility of Results; Tomography, X-Ray Computed; Trauma Severity Indices